PELAKSANAAN MEDIASI MENURUT PERMA NOMOR 1 TAHUN 2008 BERIKUT PERMASALAHANNYA - Harahap, Sholahuddin (LPPM Unisba, 2011)
In essence, every subject of law both individual and legal entity wants to life peacefully without any dispute with any other member of community. However, the dispute could not be avoided in certain circumstances, so that it has to be settled before a court. It is generally kwown thatÂ a dispute settled through the court conventionallyÂ is very slow and complicated. For this reason, it is necessary for Supreme Court to optimize a peaceful method as set out in Article 130 of HIR or Article 154 of RBG. Such method known as settlement of disputeÂ Â throughÂ Â mediation as regulated by the Supreme Court Regulation No.1 of 2008. Under the Regulation, principal the parties are obliged toÂ present in mediation. They are given the opportunity to resolve their dispute by mediation out of court to be affirmed. If the expression of a partyâs consent to be bound by an agreement has been procured through the coercion, error or fraud of its representativeÂ by another Party, the Party must submit a new claim for the purpose ofÂ agreement cancelation.